2014
DOI: 10.1186/s12862-014-0205-0
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and evolution of myxozoan minicollagens and nematogalectins

Abstract: BackgroundMyxozoa are a diverse group of metazoan parasites with a very simple organization, which has for decades eluded their evolutionary origin. Their most prominent and characteristic feature is the polar capsule: a complex intracellular structure of the myxozoan spore, which plays a role in host infection. Striking morphological similarities have been found between myxozoan polar capsules and nematocysts, the stinging structures of cnidarians (corals, sea anemones and jellyfish) leading to the suggestion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
68
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 51 publications
11
68
0
Order By: Relevance
“…These results are consistent with those of other molecular phylogenetic studies (19,23), although these have been criticized as possible artifacts of long-branch attraction (21). The monophyly of Myxozoa + P. hydriforme is also supported by endoparasitism in fish, a unique cell-within-cell developmental stage, possession of a single similar type of nematocyst (19,23), and similarity in minicollagen sequences (28). This phylogenomic pattern suggests that endoparasitism in Cnidaria was a single event that occurred at the base of Myxozoa + P. hydriforme, but that the dramatic reduction in body plan occurred following the divergence of P. hydriforme from myxozoans, as P. hydriforme retains many cnidarian features.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…These results are consistent with those of other molecular phylogenetic studies (19,23), although these have been criticized as possible artifacts of long-branch attraction (21). The monophyly of Myxozoa + P. hydriforme is also supported by endoparasitism in fish, a unique cell-within-cell developmental stage, possession of a single similar type of nematocyst (19,23), and similarity in minicollagen sequences (28). This phylogenomic pattern suggests that endoparasitism in Cnidaria was a single event that occurred at the base of Myxozoa + P. hydriforme, but that the dramatic reduction in body plan occurred following the divergence of P. hydriforme from myxozoans, as P. hydriforme retains many cnidarian features.…”
Section: Discussionsupporting
confidence: 81%
“…In recent studies, myxozoans were found to possess the cnidarian-specific minicollagen and nematogalectin genes (24,27,28), each of which has been shown to play important roles in the nematocyst structure in Hydra (29,30). These studies support previous morphology-based assertions that myxozoan polar capsules are homologous to cnidarian nematocysts (4,5,31,32) and thus indirectly suggest a close evolutionary relationship between these two groups.…”
Section: Significancesupporting
confidence: 79%
See 3 more Smart Citations